Short communication: Physiological response to drought in North Sulawesi (Indonesia) local rice (Oryza sativa) cultivars at the tissue level in hydroponic culture - Song Ai Nio; RISA JUNITA MEREH; DANIEL PETER MANTILEN LUDONG (Society for Indonesian Biodiversity, 2021)
Abstract. Nio SA, Mereh RJ, Ludong DPM. 2021. Short communication: Physiological response to drought in North Sulawesi (Indonesia) local rice (Oryza sativa) cultivars at the tissue level in hydroponic culture. Biodiversitas 22: 58-64. Water availability influenced the metabolism processes in the plants and this condition could change water balance in the cells as well as restricting the growth and production of crops. This study aimed to evaluate the effect of in vitro polyethylene glycol (PEG) 8000-induced water deficit on the relative water content and chlorophylls (total, a, and b) concentration as physiological response in leaf segments of North Sulawesi (Indonesia) local rice cultivars (cvs. Superwin, Ombong, Burungan, and Temo). The rice leaves were cut into 1 cm x 1 cm segments and were treated under both control (0 MPa) and water deficit (-0.25 and -0.5 MPa) using PEG 8000 as osmoticum. The experiment was factorial completely randomized block design with 4 sampling times (0, 4, 8, and 12 hours) and three replicates. Interaction of water deficit duration and PEG 8000 treatment resulted in a significant difference in leaf relative water content. The leaf relative water content at PEG -0.5 MPa after 8 and 12 hours of treatments was lower than at control (PEG 0 MPa) when the treatment commenced (0 hour). The concentration of chlorophylls (total, a, and b) were significant differences among cultivars and water deficit durations. This study showed that leaf relative water content was a potential physiological indicator of PEG 8000-induced water deficit in North Sulawesi local rice at the tissue level in hydroponic culture.